2015
DOI: 10.1111/vco.12166
|View full text |Cite
|
Sign up to set email alerts
|

Feline discrete high‐grade gastrointestinal lymphoma treated with surgical resection and adjuvantCHOP‐based chemotherapy: retrospective study of 20 cases

Abstract: The aim of this retrospective study was to evaluate the outcome of cats treated with surgical intervention for a discrete intermediate-/high-grade gastrointestinal lymphoma prior to CHOP-based chemotherapy. Variables including sex, breed, haematocrit, white blood cell count, serum albumin concentration, clinical stage of disease, gastrointestinal obstruction and peritonitis were assessed for their effect on survival. Twenty cats met the inclusion criteria with three cats still alive at the time of data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 17 publications
6
40
0
Order By: Relevance
“…The overall survival times in this study are comparable to those reported for cats with GI LSA treated with systemic chemotherapy alone . In addition to improving survival time, maintaining quality of life is an important goal in LSA case management because treatment is often palliative in nature.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The overall survival times in this study are comparable to those reported for cats with GI LSA treated with systemic chemotherapy alone . In addition to improving survival time, maintaining quality of life is an important goal in LSA case management because treatment is often palliative in nature.…”
Section: Discussionsupporting
confidence: 71%
“…Unlike in dogs, in which multicentric LSA predominates and is overwhelmingly responsive to chemotherapy, the response to multiagent chemotherapy in cats with feline GI large‐cell LSA is less predictable, with overall response rates ranging from 30% to 75% . Response durability also tends to be less favorable, with reported median survival times (MST) of 3 to 6 months . However, MST tends to be closely linked to response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent veterinary publication supports the combination of surgery and chemotherapy to treat feline intestinal lymphoma (Gouldin et al . ). This treatment combination has also been shown to improve overall survival of people treated for intestinal lymphoma (Kim et al .…”
Section: Discussionmentioning
confidence: 97%
“…Lymphoma is usually treated with chemotherapy unless there is perforation, the need for a biopsy or intestinal obstruction (Culp et al 2012;Selting 2013). There is, however, growing evidence in both veterinary and human literature supporting the combination of surgery with chemotherapy to treat discrete intestinal lymphoma (Kim et al 2011;Gou et al 2012;Gouldin et al 2017;Hong et al 2017).…”
Section: Introductionmentioning
confidence: 99%